2018
DOI: 10.1002/jbt.22038
|View full text |Cite
|
Sign up to set email alerts
|

Lead‐induced DNA damage and cell apoptosis in human renal proximal tubular epithelial cell: Attenuation via N‐acetyl cysteine and tannic acid

Abstract: This study investigates the exposure of lead-induced reactive oxygen species (ROS) generation, DNA damage, and apoptosis and also evaluates the therapeutic intervention using antioxidants in human renal proximal tubular cells (HK-2 cells). Following treatment of HK-2 cells with an increasing concentration of lead nitrate (0-50 μM) for 24 h, the intracellular ROS level increased whereas the GSH level decreased significantly in a dose-dependent manner. Comet assay results revealed that lead nitrate showed the ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 40 publications
1
12
0
Order By: Relevance
“…NAC is a well-established antioxidant and intracellular ROS scavenger and known to be cytoprotective against a variety of cellular damaging agents and its antioxidant activities have been established in several studies. 24,25 In the current study, we found that NAC significantly attenuated heptachlor-induced OS in HK-2 cells (Figure 4) implicating that NAC can be considered as an important therapeutic intervention against heptachlor-induced cytotoxicity in humans owing to its excellent scavenging capacity.…”
Section: Discussionmentioning
confidence: 51%
“…NAC is a well-established antioxidant and intracellular ROS scavenger and known to be cytoprotective against a variety of cellular damaging agents and its antioxidant activities have been established in several studies. 24,25 In the current study, we found that NAC significantly attenuated heptachlor-induced OS in HK-2 cells (Figure 4) implicating that NAC can be considered as an important therapeutic intervention against heptachlor-induced cytotoxicity in humans owing to its excellent scavenging capacity.…”
Section: Discussionmentioning
confidence: 51%
“…In the HSCs model in vitro , allicin treatment dramatically alleviated the lead-induced increase in ROS generation (Figure 5B). Previous study showed that Plumbum could generate DNA damage by elevating ROS level in human cells [28]. Next, we investigated whether DNA damage contributes to lead-induced HSCs aging.…”
Section: Resultsmentioning
confidence: 99%
“…For example, higher number of cell death (TUNEL positive) was evidenced in PbAc treated mice, while TL effectively protected the cell from death. This result could be due to the counteracting effect of TL against ROS mediated activation of caspase-3 and caspase-9 ( He et al, 2016 , Moneim et al, 2016 , Siddarth et al, 2018 ), exclusively by protocatechuic acid, caffeic acid and gallic acid ( Mard et al, 2015 , Trumbeckaite et al, 2017 , Yamabe et al, 2015 ). To activate caspase cascades, DNA fragmentation is a prerequisite ( McIlwain et al, 2013 ), which was actively achieved by PbAc in the kidney ( Kelainy et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%